Biomarkers for the Discrimination of Acute Kawasaki Disease From Infections in Childhood - Zandstra, Judith; van de Geer, Annemarie; Tanck, Michael W. T.; van Stijn-Bringas Dimitriades, Diana; Aarts, Cathelijn E. M.; Dietz, Sanne M.; van Bruggen, Robin; Schweintzger, Nina A.; Zenz, Werner; Emonts, Marieke; Zavadska, Dace; Pokorn, Marko; et al. (Frontiers in Pediatrics, 2020)
Background: Kawasaki disease (KD) is a vasculitis of early childhood, mimicking several infectious diseases. Differentiation between KD and infectious diseases is essential as KD’s most important complication - the development of coronary artery aneurysms (CAA) - can be largely avoided by timely treatment with intravenous immunoglobulins (IVIG). Currently, KD diagnosis is only based on clinical criteria. The aim of this study was to evaluate whether routine CRP and additional inflammatory parameters MRP8/14 (S100A8/9) and human neutrophil-derived elastase (HNE) could distinguish KD from infectious diseases. Methods and Results: The cross-sectional study included KD patients and children with proven infections as well as febrile controls. Patients were recruited between July 2006 and December 2018 in Europe and USA. MRP8/14, CRP and HNE were assessed for their discriminatory ability by multiple logistic regression analysis with backward selection and receiver operator characteristic (ROC) curves. In the discovery cohort the combination of MRP8/14+CRP discriminated KD patients (n=48) from patients with infection (n=105) with area under the ROC curve (AUC) of 0.88. HNE values did not improve discrimination. The first validation cohort confirmed the predictive value of MRP8/14+CRP to discriminate acute KD patients (n=26) from those with infections (n=150) with an AUC 0.78. The second validation cohort of acute KD patients (n=25) and febrile controls (n=50) showed an AUC of 0.72, which improved to 0.84 when HNE was included. Conclusion: When used in combination, the plasma markers MRP8/14, CRP and HNE may assist in discrimination of KD from both proven or suspected infection.